Analisis Literasi Informasi Pengguna Taman Baca Yayasan Pendidikan SDIT Al-Ikhlas Medan - Yusniah Yusniah; Hannum Angginami; Dinda Salsabilla Mahendra; Juni Yanti; Rizki Mahyani Br Hasibuan (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
Information literacy analysis of SDIT Al-Ikhlas reading garden is the focus of this research. Examination of information literacy in the reading garden of the SDIT Al-Ikhlas educational foundation is the subject of this study. Through direct interviews and documentation, this study used a qualitative research approach. Based on the findings of this study, children's magazines, math and science comics, and children's magazines are types of children's collection materials that can be found in reading gardens. Children's comics are the type of children's collection material that is most often read and used, while children's magazines are the type of children's collection material that is rarely used or read. Keywords: Literacy, Information, Reading Center of Sdit Al- Ikhlas Medan